Designing a Geometry Examination Framework to Evaluate Higher-Order Thinking Skills - Kania, Nia; Nurhikmayati, Iik; Larsari, Vahid Norouzi (International Journal of Geometry Research and Inventions in Education, 2025)
This study aims to develop a valid, practical, and effective instrument for assessing higher-order thinking skills (HOTS) in junior high school mathematics. Employing a research and development (R&D) approach, the study adapts Mardapi's (2008) development model, which includes nine stages. However, this research focuses on the first seven stages, leaving the final implementation to teachers in schools. The instrument was tested on 40 students at SMPN 2 Rajagaluh, Majalengka Regency. The validity analysis demonstrated that all V values exceeded 0.3, indicating strong content validity. Reliability testing yielded a Cronbach's Alpha score of 0.52, suggesting moderate internal consistency. The findings revealed that students' HOTS performance remains suboptimal, highlighting the need for targeted instructional strategies. Strengthening HOTS can be achieved through structured practice with complex problem-solving tasks. This study provides a robust framework for educators to assess and enhance students’ critical thinking abilities in mathematics.